PREDIKSI FINANCIAL DISTRESS DENGAN MENGGUNAKAN MODEL ALTMAN (Z-SCORE) DAN ZMIJEWSKI (X-SCORE) (Studi pada Perusahaan Rokok yang Terdaftar di Bursa Efek Indonesia Periode 2014-2016) - Indriani, Firda Rahayu (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2018)
This study aims to determine and predict the onset of financial distress using Altman Z-Score and Zmijewski’s X-Score on cigarette companies listed in the Indonesia Stock Exchange (IDX) in the period of 2014-2016. Altman Z-Score detects financial distress and bankruptcy on companies using five financial ratios; they are working capital to total assets, retained earnings to total assets, earnings before interest and tax to total assets, market value of equity to book value of liabilities, and sales to total assets. Meanwhile, Zmijewski’s X-Score uses three financial ratios; they are return on Assets, debt ratio, and current ratio. This descriptive research uses quantitative approach. The data are secondary in forms of companies’ financial statements. The results show that both prediction models have similar results. Of the four tobacco companies being studied, three companies are in safe zone during the three-year research period. Furthermore, one company is predicted to experience financial difficulties and have bankruptcy potential in 2014 and 2015 and bounce back to safety in 2016. Keywords: Altman Z-Score, Zmijewski X-Score, financial distress